Argentina: two faces of the small and medium bourgeoisie - Petras, James F. (Contemporary crises, 1989)
Research focused on the socio-economic and political attitudes of the medium and small bourgeois in Argentina during the Alfonsin Presidency. Data reveals clear position critical of the pro-big business orientation of the regime. However because of their shift away from productive activity towards the speculative, because of the increasing dependence on illegal sources of income (the underground economy), the small and medium size bourgeoisie were shifting toward the neo-liberal Right as a means of "legalizing" their income.